2018
DOI: 10.1111/jfbc.12596
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, brine shrimp lethality and analgesic properties of propolis from Bangladesh

Abstract: Propolis which is a natural resinous product from the honeybees, is becoming increasingly popular for its diverse therapeutic and industrial applications. In this study, we report for the first time the antioxidant, cytotoxic, and antinociceptive activities of propolis from Bangladesh (BDP). The antioxidant activities were measured by biochemical analyses while cytotoxicity was evaluated by brine shrimp lethality bioassay. Analgesic activity was evaluated by tail immersion and acetic acid‐induced writhing mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The phenolics (including gallic acid, benzoic acid, salicylic acid, and pyrogallol), flavonoids (rutins), antioxidant vitamins (ascorbic acids and tocopherols), and others antioxidants/antiradicals in the ethanolic extract of Bangladeshi propolis (Tanvir et al, 2018) have synergistic effects which confer protection against TTC-induced histopathological alterations, and this may be via scavenging of free radicals and the regulation of cholesterol levels, which is consistent with the biochemical findings. The study lacks to establish any potential toxic effects of propolis in rats.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The phenolics (including gallic acid, benzoic acid, salicylic acid, and pyrogallol), flavonoids (rutins), antioxidant vitamins (ascorbic acids and tocopherols), and others antioxidants/antiradicals in the ethanolic extract of Bangladeshi propolis (Tanvir et al, 2018) have synergistic effects which confer protection against TTC-induced histopathological alterations, and this may be via scavenging of free radicals and the regulation of cholesterol levels, which is consistent with the biochemical findings. The study lacks to establish any potential toxic effects of propolis in rats.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of this study have indicated that propolis has potential protective effects against renal damage induced by toxic levels of TTC in animals. It is plausible that the presence of bioactive phenolic acids, flavonoids, tocopherol, and ascorbic acids in Bangladeshi propolis (Tanvir et al, ), may confer nephroprotection in animals, as reported in another study involving Croatian propolis on diabetic nephropathy (Oršolić et al, ), where antioxidant potential of the propolis have also been highlighted.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations